2019
DOI: 10.3324/haematol.2018.207092
|View full text |Cite
|
Sign up to set email alerts
|

Latexin regulation by HMGB2 is required for hematopoietic stem cell maintenance

Abstract: regulation by HMGB2 is required for hematopoietic stem cell maintenance. ABSTRACTHematopoietic stem cells provide life-long production of blood cells and undergo selfrenewal division in order to sustain the stem cell pool. Homeostatic maintenance of hematopoietic stem cell pool and blood cell production is vital for organismal survival. We previously reported that latexin is a negative regulator of hematopoietic stem cells in mice, whose natural variation in the expression is inversely correlated with hematopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…Emerging evidence has indicated that epigenetic regulation acts as a driver of tumorigenesis by regulating stem-like features of CSLCs 6,7. Aberrant DNA methylation can promote progression of OS 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has indicated that epigenetic regulation acts as a driver of tumorigenesis by regulating stem-like features of CSLCs 6,7. Aberrant DNA methylation can promote progression of OS 8,9.…”
Section: Introductionmentioning
confidence: 99%
“…This report is the first demonstration that genetic variation, especially SNP, is a determinant for the variations among different mouse strains in HSC pool size and function. The authors also discussed a similar observation made in humans, 11 opening the possibility that the genetic variation in the Lxn gene promoter region may contribute to the pathogenesis of hematopoietic aplasia/neoplasia, such as bone marrow failure or leukemia. If epigenetic regulation of Lxn gene transcription is involved in these hematopoietic diseases, it could be a new therapeutic target for genetic correction/modification such as genome editing.…”
mentioning
confidence: 69%
“…[4][5][6][7] These developments are enabling detailed characterization of normal and disordered human erythropoiesis. [8][9][10][11][12][13] Importantly, as a result of this progress it is now possible to obtain insights into at what stage of the complex process of erythroid differentiation various genes contribute to ineffective erythropoiesis.…”
Section: Staying Hydrated Is Important Also For Erythroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB2 is ubiquitous and ample in eukaryotic cells, and regulating proliferation serve as its primary function. HMGB2 could regulate latexin to keep hematopoietic stem cell proliferation and differentiation 55 . In articular cartilage, loss of HMGB2 reduces the regeneration capacity of mesenchymal stem cells by increasing apoptosis 56 .…”
Section: Discussionmentioning
confidence: 99%